Is China decoupling from the global value chain? A quantitative analysis framework based on the global production network - Chuke Jiang; Lizhi Xing (Humanities & Social Sciences Communications)
Abstract In recent years, frequent global emergencies have disrupted international stability and prompted countries to decouple from Global Value Chain (GVC), raising critical questions about how to restore and manage the extent of such decoupling to mitigate risks. From a systems science perspective, this paper constructs a Global Industrial Value Chain Network model based on Multi-Regional Input-Output data and proposes a theoretical framework for quantitatively assessing the degree of decoupling of economies and industries within GVC. Using the U.S.’s new trade remedy measures as a case study, the paper analyzes their impact on China and key “transit” countries involved in global trade networks. The analysis reveals that industries heavily engaged in intermediate goods trade exhibit greater stability in the face of global disruptions compared to resource-based sectors. Moreover, highly integrated, advanced economies demonstrate strong resilience by effectively leveraging external resources. Despite the impacts of the COVID-19 pandemic, China’s GVC connections have been reinforced, reflecting its adaptive capacity. The findings also indicate that China’s emphasis on domestic circulation has enhanced its ability to withstand Western trade challenges. Furthermore, multilateral trade agreements and “backdoor” export strategies serve as effective short-term measures to circumvent U.S. trade restrictions.